ANALISIS PELUANG PENGGUNAAN LAYANAN KEUANGAN DIGITAL (LKD) PADA MASYARAKAT KABUPATEN ACEH BESAR PROVINSI ACEH - Chenny Seftarita; Uliya Azra (JURNAL EKOMBIS, 2018)
This research to determine the willingness of the public who want use digital  financial services. this research was conducted in Aceh Besar Regency  by  taking200 samples randomly in several villages. The model used in this research is a logit model. The results of research showed that of the variable income, distance to the center of the economy, distance to the nearest bank, and a signal service, there is only one variable is significant and positive impact on the desire to use financial services digital, variable distance to the nearest bank while a variable distance to the center of the economy negative and not significant. Based on the research that has been done, a lot of people who  are  less  aware  Financial Services Digital and  some people still make less use of  banking services. Researchers recommended that the government and Bank Indonesia participated socialize the Financial Services Digital.Keyword : Aceh Besar, Digital financial services, Logit modeteks